2004
DOI: 10.1080/00015550410026948
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Increased Skin Cancer Risk in Psoriasis Patients Treated with Broadband or Narrowband UVB Phototherapy: A First Retrospective Study

Abstract: Phototherapy of skin diseases such as psoriasis is an effective and safe treatment modality. However, increasing the risk of skin cancer by phototherapy is a serious concern. An increased skin cancer risk occurs after prolonged photochemotherapy (PUVA). In contrast, the role of broadband UVB or narrowband UVB therapy in skin carcinogenesis of humans with psoriasis is less clear. Therefore, we investigated the incidence of skin tumours in a total of 195 psoriasis patients, receiving broadband (n=69) or narrowba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(37 citation statements)
references
References 34 publications
0
35
0
2
Order By: Relevance
“…Thus, phototherapy utilizing the energy of photons in combination with photosensitizers can be used to direct the energy to generate ROS or DNA damage in the tissue specific manner seems to be a promising alternative for treatment of advanced breast cancer patients for whom the RT is limited due to prior therapies. There is a recent development of targeted phototherapy, photosensitizers [47,48] that further minimizes the toxicities associated with UV phototherapy. Ionizing radiation enhances both epithelial growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) expression, and similar results were obtained with UV radiation [23,49], which are a part of key pathways for tumor progression and radioresistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, phototherapy utilizing the energy of photons in combination with photosensitizers can be used to direct the energy to generate ROS or DNA damage in the tissue specific manner seems to be a promising alternative for treatment of advanced breast cancer patients for whom the RT is limited due to prior therapies. There is a recent development of targeted phototherapy, photosensitizers [47,48] that further minimizes the toxicities associated with UV phototherapy. Ionizing radiation enhances both epithelial growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) expression, and similar results were obtained with UV radiation [23,49], which are a part of key pathways for tumor progression and radioresistance [16].…”
Section: Discussionmentioning
confidence: 99%
“…These unnecessary exposures of uninvolved skin increase the risk of short- and long-term side effects such as blistering, pruritus and photoaging. In a retrospective study with a total of 195 psoriasis patients, no evidence for elevated carcinogenesis after narrow-band UVB phototherapy was found [15]. In several studies the efficacy of the excimer laser has been demonstrated [5, 8, 16].…”
Section: Discussionmentioning
confidence: 99%
“…However, the cumulative dose of NB-UVB light is very low, and the carcinogenic potential of these doses is likely to be negligible [2]. …”
Section: Discussionmentioning
confidence: 99%
“…In fact, NB-UVB is effective, well tolerated and does not present systemic toxicity, thus ensuring a remarkably low toxicity profile when used in combination with a systemic drug such as efalizumab. Indeed, when a short treatment cycle of NB-UVB phototherapy is used, the hazards of skin carcinogenesis and photoaging are negligible [2], and the inconvenience for the patient who must attend the photobiology unit is limited. The possible usefulness of this combination was previously demonstrated in a case report where a psoriatic flare during continuous treatment with efalizumab was reported to be successfully managed with NB-UVB [3].…”
Section: Introductionmentioning
confidence: 99%